Cinta Semanis IBU - Ain Maisarah; Nurismaliza Ismail; Aman Wan; Anis Hazirah; Fauzia Chang; Hadi Sumarna; Danial Hakim (Batu Caves, Selangor : BLINK BOOK SDN BHD, 2018)
A compilation of three comics and one novel
Keywords: Children's stories, Malay; Malay fiction; Comic books, strips, etc